Proceedings of the 8th International Conference on Electronic Commerce the New E-Commerce: Innovations for Conquering Current B 2006
DOI: 10.1145/1151454.1151474
|View full text |Cite
|
Sign up to set email alerts
|

Capacity allocation with competitive retailers

Abstract: This paper addresses a problem in supply chain management that how scarce resources can be efficiently allocated among competing interests. We present a formal model of allocation mechanisms for such settings that a supplier with limited production capacity allocates its products to a set of competitive retailers. In contrary to the existing allocation mechanisms in which retailers are local monopolists, the new model exhibits much more complicated market behaviors. We show that the widely-used proportional al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Under proportional allocation, the retailers inflate orders to be allocated more than competitors. Contrary, we showed that uniform allocation induces truthful order quantity from the retailers under which we have the same equilibrium price as Furuhata and Zhang [11].…”
Section: Heterogeneous Allocationsmentioning
confidence: 54%
See 4 more Smart Citations
“…Under proportional allocation, the retailers inflate orders to be allocated more than competitors. Contrary, we showed that uniform allocation induces truthful order quantity from the retailers under which we have the same equilibrium price as Furuhata and Zhang [11].…”
Section: Heterogeneous Allocationsmentioning
confidence: 54%
“…In this case, according to Theorem 6, we are easily able to obtain the equilibrium order quantity m * i =m i . The interesting case of the capacity range is K ≤ and the equilibrium price p * = P (K), which is the same price as the quantity competition shown in [11]. If it is asymmetric, we obtain allocation g i (m…”
Section: Theorem 6 There Does Not Exist An Order Equilibriummentioning
confidence: 94%
See 3 more Smart Citations